In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

In situ synthesis and surface functionalization of gold nanoparticles with curcumin and their antioxidant properties: an experimental and density functional theory investigation - Singh, Dheeraj K.; Jagannathan, Ramya; Khandelwal, Puneet; Abraham, Priya Mary; Poddar, Pankaj (Nanoscale, 2013)
Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is an active component of turmeric; it is responsible for its characteristic yellow color and therapeutic potential, but its poor bioavailability remains a major challenge. In order to improve the bioavailability of curcumin, various approaches have been used. One of the possible approaches to increase the bioavailability of curcumin is its conjugation on the surface of metal nanoparticles. Therefore, in the present study, we report the binding of curcumin on the surface of gold nanoparticles (AuNPs). The AuNPs were synthesized by the direct reduction of HAuCl4 using curcumin in the aqueous phase, without the use of any other reducing agents. We found that curcumin acts both as a reducing and capping agent, stabilizing the gold sol for many months. Moreover, these curcumin-capped AuNPs also show good antioxidant activity which was confirmed by the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical test. Thus, the surface functionalization of AuNPs with curcumin may pave a new way of using the curcuminoids towards possible drug delivery and therapeutics. Apart from the experimental study, a detailed quantum chemical calculation using density functional theory (DFT) has been performed, in order to investigate the formation of a complex of curcumin with Au3+ ions in different possible conformational isomeric forms. Our theoretical calculations indicate the evidence of electron transfer from curcumin into the Au center and essentially indicate that as a consequence of complexation, Au3+ ions are reduced to Au-0. Our theoretical results also propose that it is the breakage of intramolecular H-bonding that probably leads to the increased availability of curcumin in the presence of gold ions and water molecules.